Front St. decorated with American flags for celebration, Nome, Alaska, approximately 1900. - Hegg, Eric A., 1867-1948 (1900)
Shows The Hunter saloon and The Pioneer saloon to the left. Caption on image: "Nome, Alaska" Original image in Hegg Album 38, page 8